Overview of changes in the health sector and its financing in the Republic of Serbia in the period 2004-2020 - Gajić-Stevanović Milena; Stevanović Ivan (Serbian Medical Society - Dental Section, Belgrade, 2023)
Introduction In the period from 2004 to 2020, many reforms were implemented in the health sector of the Republic of Serbia and it's financing. The aim of this work was to provide an insight into foundations on which healthcare was based in the Republic of Serbia in the period from 2004 to 2020 and review the reform changes in the healthcare sector and it's financing. Material and method A retrospective analysis of data from the National Health Account of the Institute of Public Health of Serbia, the regulations of the Republic Health Insurance Fund, reports of the Ministry of Health as well as laws and regulations related to the health sector was performed. Results The results of the analysis showed that the State health sector represented the foundation of the health system in the Republic of Serbia in the observed period. Of the total health financing, it was estimated that about sixty percent were public financing schemes, and about forty percent belonged to private schemes, with a large part of private schemes being out-of-pocket payments. Conclusion The general conclusion of the analysis is that in the observed period, within the framework of the reform changes, Serbia had a good system of exemption from participation, but that out-of-pocket payments for certain health services and corrupt payments represented a barrier to health care.